High Stability and Uniformity Polymeric Thin-Film Transistor Arrays Fabricated by Directly Subtractive Photolithography. (13th April 2018) - Xie, Yingtao; Wang, Dongping; Li, Miao; Cui, Wei; Wang, Lu; Yan, Zhonghua; Wang, Huadong; Guan, Chun; Chen, Guoping; He, Feng
Abstract: Based on standard photolithography, it was demonstrated that an added processing of oxygen plasma treatment to polymeric film was effective to reduce off-current of patterned OTFT device and improve the adhesion between photoresist and polymeric film before spin-coating. And then two procedures were introduced to obtain better performance during the patterned OSC layer. As a result, the procedure of hard-baking photoresist and then dry-etching can prevent oxygen plasma from swelling to the semiconductor film to obtain better performance. Most importantly, the high stability and uniformity OTFT device arrays were fabricated via the modified photolithography processing. Firstly, the transfer curve of OTFT with 5 months later showed any non-degradation compared to the characteristics of the fresh OTFT device. The reason may be that the photoresist on OSC channel can protect OSC from the H2 O in air. Secondly, the low threshold voltage shift under positive and negative bias stress test showed low charge trapping in the semiconductor/dielectric interface region. Finally the method was applied to fabricate polymeric OTFTs arrays on the 4-inches wafer with features down to 10 μm. As a result, it demonstrated the excellent uniformity, which is high mobility of 0.24–0.31 cm 2 V −1 s −1, low threshold voltage shift of −5 to −3V, and ion/off ratio of 10 8 –10 10 .